THE PHENOMENON OF FORENSIC INITIATIVE CONCEPT AND CURRENT PROBLEMS OF ITS IMPLEMENTATION IN A DIGITAL SOCIETY - Nedashkivska, O. (Theory and Practice of Forensic Science and Criminalistics, 2020)
The author addresses the issue of taking forensic initiative by forensic experts which is connected with a failure to recognize the mechanism for its implementation in practice, peculiarities and specifics in the activities of various participants of criminal proceedings. The Research purpose is to analyze current regulatory framework that regulates the right to forensic initiative and various scientific opinions on the right to manifest forensic initiative as a phenomenon, its significance for forensic examination in general as well as a systematic reflection of practical problems on application of forensic initiative right by forensic experts while practical work, characteristic forms of its manifestation. The study was conducted by questioning forensic experts from the Ministry of Internal Affairs of Ukraine in order to determine boundaries of possessing knowledge in the conceptual framework in forensic initiative field, to determine the attitude of forensic experts to the very concept of forensic initiative, their use of own law-regulated forensic initiative, analysis of existing scientific approaches and use forms of the right of forensic initiative. The boundaries of possession and handling of theoretical and practical knowledge in the field of forensic initiative and their implementation in practice are established by forensic experts of the Ministry of Internal Affairs. Various scientific approaches to the problem of forensic initiative manifestation are reflected and analyzed in conditions of society current development, practical significance and importance of ensuring realization of the right to forensic initiative by forensic experts in their practical work is outlined. A systematic solution for the problem is suggested: development of an appropriate regulatory framework that would regulate the procedure for using the right to forensic initiative and creation of an algorithm for implementing such a right of a forensic expert in practice, which will take forensic examination to a qualitatively new level and ensure thoroughness and comprehensiveness of research, facilitate formation of the rule of law.